Beneficial effect of synbiotics on experimental colon cancer in rats - Gavresea, Fani; Vagianos, Costas; Korontzi, Maria; Sotiropoulou, Georgia; Dadioti, Petroula; Triantafillidis, John K.; Papalois, Apostolos E. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The aim of this study was to investigate the influence of a synbiotic preparation (a mixture of six probiotics and a prebiotic) on aberrant crypt foci (ACF) formation, dysplasia, inflammation, and colitis-like lesions in experimental colon cancer in rats. Materials and Methods: Sixty male rats were categorized into three groups of 20 animals each. Group A was administered 1,2-dimethylydrazine, 15 mg/kg body weight (BW), once a week for 2 weeks. Group B was administered 1,2-dimethylydrazine at the same dose plus synbiotic, started after the second dose of carcinogen and lasted for 5 weeks. Group C was administered synbiotic plus carcinogen from the beginning of the experiment and lasted for 7 weeks. Animals were killed at the end of week 7. Results: At the end of the experiment, the animals that received carcinogen plus the synbiotic had 100%, whereas the animals that received only carcinogen has 70% survival. Animals of groups B and C had significantly lower percentage of inflammation, colitis-like lesions, and ACF dysplasia than animals of group A, whereas those of group C had the least pathological lesions. Conclusion: Synbiotics seem to protect against the appearance of preneoplastic colon lesions in rats. The results of this experimental study suggest that treatment with a synbiotic preparation exerts significant antimutagenic properties against the development of preneoplastic lesions in rats. Cite this article as: Gavresea F, Vagianos C, Korontzi M, et al. Beneficial effect of synbiotics on experimental colon cancer in rats. Turk J Gastroenterol 2018; 29: 494-501.